Pengembangan Sistem Pelaporan Kecelakaan Lalu Lintas berbasis Web (Studi Kasus : Polres Magetan) - Irma Nurdianingtyas; Achmad Arwan; Denny Sagita Rusdianto (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Polres Magetan is a resort police in the Magetan district which is led by the Kapolres. Under the Kapolres there are several elements of the unit. One of them is the traffic unit that has the task of carrying traffic turjawali, service registration of vehicles, investigations of traffic accidents and law enforcement in the traffic sector. When handling traffic accident, first public report to the nearest police station, so it takes a long time to help the accident victim if the accident scene is far away. When handling traffic accidents, police officers process the scene of the case by collecting traffic accident data and recording it on paper to be used as a police report for further investigation. It makes the process of handling a traffic accident less effective. To solve this problem, a system was built to make it easier for the public to report traffic accidents and to make it easier for police officers to carry out their duties to handle and investigate traffic accidents. The system is built with the waterfall development method on a web platform with progressive web application technology to provide easy access to the system. The system is implemented using a codeigniter framework with the concept of Model View Controller (MVC). The system is tested using unit testing, integration testing and validation testing resulted 100% valid, which means that it runs according to its functionality. The results of the compatibility test show that there are no critical issues so that it meets the compatibility aspect and can run on various browsers.